Principles of managerial finance - Gitman, Lawrence J. (Harper & Row, 1988)
With explanations and real-life case studies, combined with an extensive array of aids to learning, this introductory text integrates features which provide a framework to help students learn the major concepts behind managerial finance. Learning goals are outlined at the beginning of each chapter, reviewed point-by-point at the end of the chapters and noted in the assignment material. More logically, the chapter on the analysis of financial statements is now placed immediately after the chapter on financial statements, enabling students to use rational analysis to interpret material while it is still fresh in their minds. An instructor's manual is also available.